EVALUATION OF DERMATOPHYTIC AND NON DERMATOPHYTIC CAUSE OF SKIN INFECTION IN A TEACHING HOSPITAL - PRIYANKA MENON,; ABHISEK ROUTRAY, (International Journal of Pharma and Bio Sciences, 2015)
A skin infection due to dermatophytes has become a significant health problem affecting children, adolescents and adults. The present study was undertaken from January 2013 to December 2013 to study the clinical pattern and etiological agents of dermatophytic infection. Out of 147 seen samples collected, 73 were culture positive. Among culture positive 31 were dermatophytes (42.46%) and 42 were non - dermatophytes (57.53%).The current study emphasizes on both dermatophytic and non dermatophytic cause of various fungal skin infection which indeed helps in understanding the fungal infection pattern seen in different patients and choosing appropriate antifungal agent.